An insight into a sustainable removal of bisphenol a from aqueous solution by novel palm kernel shell magnetically induced biochar: synthesis, characterization, kinetic, and thermodynamic studies - Katibi, Kamil Kayode; Yunos, Khairul Faezah; Che Man, Hasfalina; Aris, Ahmad Zaharin; Mohd Nor, Mohd Zuhair; Azis, Rabaah Syahidah (Multidisciplinary Digital Publishing Institute, 2022)
Recently Bisphenol A (BPA) is one of the persistent trace hazardous estrogenic contaminants in the environment, that can trigger a severe threat to humans and environment even at minuscule concentrations. Thus, this work focused on the synthesis of neat and magnetic biochar (BC) as a sustainable and inexpensive adsorbent to remove BPA from aqueous environment. Novel magnetic biochar was efficiently synthesized by utilizing palm kernel shell, using ferric chloride and ferrous chloride as magnetic medium via chemical co-precipitation technique. In this experimental study, the influence of operating factors comprising contact time (20–240 min), pH (3.0–12.0), adsorbent dose (0.2–0.8 g), and starting concentrations of BPA (8.0–150 ppm) were studied in removing BPA during batch adsorption system using neat biochar and magnetic biochar. It was observed that the magnetically loaded BC demonstrates superior maximum removal efficiency of BPA with 94.2%, over the neat biochar. The functional groups (FTIR), Zeta potential, vibrating sample magnetometer (VSM), surface and textural properties (BET), surface morphology, and mineral constituents (FESEM/EDX), and chemical composition (XRD) of the adsorbents were examined. The experimental results demonstrated that the sorption isotherm and kinetics were suitably described by pseudo-second-order model and Freundlich model, respectively. By studying the adsorption mechanism, it was concluded that π-π electron acceptor–donor interaction (EAD), hydrophobic interaction, and hydrogen bond were the principal drives for the adsorption of BPA onto the neat BC and magnetic BC.